2012
DOI: 10.1037/a0027824
|View full text |Cite
|
Sign up to set email alerts
|

The dilemma of the wounded healer.

Abstract: The wounded healer is an archetype that suggests that a healer's own wounds can carry curative power for clients. This article reviews past research regarding the construct of the wounded healer. The unique benefits that a psychotherapist's personal struggles might have on work with clients are explored, as well as the potential vulnerability of some wounded healers with respect to stability of recovery, difficulty managing countertransference, compassion fatigue, and/or professional impairment. The review als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
146
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(157 citation statements)
references
References 59 publications
6
146
0
3
Order By: Relevance
“…(Jack) Participants had to hide part of their identity, developing "unintegrated" identities. This is reminiscent of Bassman (2001) and Linehan (2011), both of whom waited until late in their professional careers before disclosing their mental distress, and Zerubavel and Wright (2012) who suggested that one's competence is less easily challenged by disclosure once it has become well established. Participants of the present study were aware of other service user professionals who did not disclose:…”
Section: "Unintegrated" Identitymentioning
confidence: 99%
“…(Jack) Participants had to hide part of their identity, developing "unintegrated" identities. This is reminiscent of Bassman (2001) and Linehan (2011), both of whom waited until late in their professional careers before disclosing their mental distress, and Zerubavel and Wright (2012) who suggested that one's competence is less easily challenged by disclosure once it has become well established. Participants of the present study were aware of other service user professionals who did not disclose:…”
Section: "Unintegrated" Identitymentioning
confidence: 99%
“…Jung was the first psychotherapist who, inspired by the mythological hero, talked about the archetype of the wounded healer and he explored applications to psychology (Jackson, 2001;Kirmayer, 2003 as cited in Zerubavel & Wright, 2012). Although minimal academic attention has been given to the wounded healer construct, it has been well documented that many psychotherapists have a history of pain or suffering (Barnett, 2007;Farber, Manevich, Metzger, & Saypol, 2005 as cited in Zerubavel & Wright, 2012).…”
Section: Please Scroll Down For Articlementioning
confidence: 96%
“…Jung was the first psychotherapist who, inspired by the mythological hero, talked about the archetype of the wounded healer and he explored applications to psychology (Jackson, 2001;Kirmayer, 2003 as cited in Zerubavel & Wright, 2012). Although minimal academic attention has been given to the wounded healer construct, it has been well documented that many psychotherapists have a history of pain or suffering (Barnett, 2007;Farber, Manevich, Metzger, & Saypol, 2005 as cited in Zerubavel & Wright, 2012). Prior research, exploring the influence of the therapist's woundedness on therapy, indicates many positive elements, such as empathic connection, deeper understanding, greater faith in the therapeutic process (Gelso & Hayes, 2007;Gilroy, Caroll & Murra, 2001as cited in Zerubavel & Wright, 2012) and, potentially, promoting self-healing within the client (Miller & Baldwin, 2000;Sedgwick, 2001as cited in Zerubavel & Wright, 2012.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Observations in the psychotherapy literature suggest many people are attracted to the helping professions through their childhood experiences of woundedness [19,20]. Did the little helper grow up to be a professional carer?…”
Section: Adverse Childhood Experiencesmentioning
confidence: 99%
“…They project their suffering on to their patients. They treat patients, they do not identify with being a patient themselves ( [13], p. 94; [20]). Sometimes the lives of healthcare professionals get so out of balance through caring too much for others and not caring enough for themselves that they become sick and burnout [25].…”
Section: Burnout and Self-carementioning
confidence: 99%